Dynamic Supraspliceosomes Are Assembled on Different Transcripts Regardless of Their Intron Number and Splicing State - Sebbag-Sznajder, Naama; Brody, Yehuda; Hochberg-Laufer, Hodaya; Shav-Tal, Yaron; Sperling, Joseph; Sperling, Ruth (Frontiers in Genetics, 2020)
Splicing and alternative splicing of pre-mRNA are key sources in the formation of diversity in the human proteome. These processes have a central role in the regulation of the gene expression pathway. Yet, how spliceosomes are assembled on a multi-intronic pre-mRNA is at present not well understood. To study the spliceosomes assembled in vivo on transcripts with variable number of introns, we examined a series of three related transcripts derived from the β-globin gene, where two transcript types contained increasing number of introns, while one had only an exon. Each transcript had multiple MS2 sequence repeats that can be bound by the MS2 coat protein. Using our protocol for isolation of endogenous spliceosomes under native conditions from cell nuclei, we show that all three transcripts are found in supraspliceosomes – 21 MDa dynamic complexes, sedimenting at 200S in glycerol gradients, and composed of four native spliceosomes connected by the transcript. Affinity purification of complexes assembled on the transcript with most introns (termed E6), using the MS2 tag, confirmed the assembly of E6 in supraspliceosomes with components such as Sm proteins and PSF. Furthermore, splicing inhibition by spliceostatin A did not inhibit the assembly of supraspliceosomes on the E6 transcript, yet increased the percentage of E6 pre-mRNA supraspliceosomes. These findings were corroborated in intact cells, using RNA FISH to detect the MS2-tagged E6 mRNA, together with GFP-tagged splicing factors, showing the assembly of splicing factors SRSF2, U1-70K, and PRP8 onto the E6 transcripts under normal conditions and also when splicing was inhibited. This study shows that different transcripts with different number of introns, or lacking an intron, are assembled in supraspliceosomes even when splicing is inhibited. This assembly starts at the site of transcription and can continue during the life of the transcript in the nucleoplasm. This study further confirms the dynamic and universal nature of supraspliceosomes that package RNA polymerase II transcribed pre-mRNAs into complexes composed of four native spliceosomes connected by the transcript, independent of their length, number of introns, or splicing state.